1988
DOI: 10.1002/aja.1001810105
|View full text |Cite
|
Sign up to set email alerts
|

Developmental heterogeneity of mesenchymal glycosaminoglycans (GAG) distribution in chick embryo lung anlagen

Abstract: The presence and distribution of mesenchymal components in the extracellular matrix during lung development in the chick embryo (from 5 1/2/6 to 18 incubation days) has been examined histochemically. Attention is focused mainly on glycosaminoglycans (GAG). Morphological reconstructions show three main stages: first (5 1/2/6-8 days), formation of 2nd-order branching; second (9-12 days), proliferation of parabronchi and third (from 13th day on), formation of air capillaries. In the first phase, hyaluronic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…Secondary bronchi (both ventrobronchi and dorsobronchi) continued to elongate and branch from and around the main bronchi until HH33, when additional branching from the primary bronchus could not be discerned and other structures such as the air sacs and recurrent bronchi became evident. These observations of the airways visualized using E-cadherin staining are consistent with descriptions gleaned from previously published work using cedar oil or alcian blue histochemistry (Locy and Larsell, 1916a; Locy and Larsell, 1916b; Becchetti et al, 1988). …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Secondary bronchi (both ventrobronchi and dorsobronchi) continued to elongate and branch from and around the main bronchi until HH33, when additional branching from the primary bronchus could not be discerned and other structures such as the air sacs and recurrent bronchi became evident. These observations of the airways visualized using E-cadherin staining are consistent with descriptions gleaned from previously published work using cedar oil or alcian blue histochemistry (Locy and Larsell, 1916a; Locy and Larsell, 1916b; Becchetti et al, 1988). …”
Section: Resultssupporting
confidence: 89%
“…All cultured explants initially contained one or two secondary bronchi on each primary bronchus. This tight control over the initial morphology of the explants ensured that morphogenesis was limited to monopodial branching from the primary bronchi, and did not include the additional branching or anastomosis of secondary bronchi characteristic of later developmental stages (Figure 1) (Locy and Larsell, 1916a; Locy and Larsell, 1916b; Becchetti et al, 1988). Whereas development of the initial branching pattern of the lung is completed in less than three days in vivo (E4+ to E7), lungs cultured ex vivo developed more slowly.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that GAG synthesis in vivo alters with development, suggesting that GAGs play a role in organogenesis. Hyaluronan is prominent early in lung morphogenesis and is mostly localized in the growing areas of the lung, whereas chondroitin sulfate proteoglycans are deposited in areas of second order branching (Becchetti et al, 1988). Inhibitors of GAG synthesis such as 6-diazo-5-oxo-L-norleucine and azaserine inhibit branching morphogenesis of cultured embryonic lung rudiments (Spooner et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the extracellular glycosaminoglycans (GAGs) varies during different phases of lung development and influence branching and differentiation of lung epithelium (Becchetti et al, 1988, Shannon, 1994.…”
Section: Reciprocal Interactions Of Developing Lung Tissuesmentioning
confidence: 99%